Demonologia słowiańska Jana Wagilewicza. Przyczynek do badań nad niewydanym dziełem XIX-wiecznej etnografii - Góra, Barbara (Przegląd Wschodnioeuropejski, 2025)
The article is a preliminary discussion of Slavic Demonology by Jan Wagilewicz (1811-1866), a prominent 19th-century Galician researcher of the Slavic past. Despite its scholarly significance, this work remains unpublished and largely unrecognized. The author of the article presents a literature review, Wagilewicz’s manuscripts and publications on demonological topics, and later issues with identifying some of these texts. Furthermore, she discusses examples where Adam Mickiewicz incorporated Wagilewicz’s published works into lectures at the Collège de France, as well as Oskar Kolberg’s use in Lud. By examining studies of literature in various languages and conducting archival research at the Vasyl Stefanyk National Scientific Library of Ukraine in Lviv, she contemplates the true shape of Wagilewicz’s Slavic Demonology. She suspects that the primary manuscript of the work remains undiscovered and should still be sought after.